Capital social, pluriatividade e desenvolvimento local : tratos e retratos no sudoeste da Bahia - Rocha, Gabriela Silveira (2016)
The modernization of agriculture, the integration of the agricultural sector to other sectors of the economy, the emergence of new activities added to the rural economy as it adapts to economic restructuring, and the emergence of new ruralities has changed labor relations and modified the organization of family farming. Based on these changes, the notion of pluriactivity came to be used to understand the multiplicity of forms that labor occur inside and outside of property. Pluriactivity incorporates concepts of productive diversification and part-time farming; pluriactivies are carried out by all members of the household, including self-employed, wage and non-wage labor, performed on and / or outside the farm. In this sense, social capital emerges as a facilitator of the development of pluriactivity. Social capital is based on social organization, trust, norms and systems that are established within the family or between existing communities in order to promote, through coordinated actions, efficiency. Thus, this research assumes that social capital is one of the elements for successful development of pluriactivity and local / rural development. Viewed in this context, this study analyzes the impact of pluriactivity and social capital used by pluriactive families to combat rural poverty and stimulate local development in seven municipalities (Anagé, Campo Belo, Barra do Choça, Caraíbas, Planauto , Tremedal, Vitória da Conquista) Sudoeste Bahiano Victory Identity. To achieve this goal, a theoretical framework based on authors of Geography, Economy and Rural Sociology discussing the categories land, capital, local / endogenous development and pluriactivities was constructed. The thesis sought theoretical support in Raffestin, Haesbaert, Sen, Amaral Filho, Schneider among others, to discuss how the territory can be used by actors to generate better living conditions and combat rural poverty. Indirect research instruments were used (data collection in public institutions and agencies) as well as direct methods (operationalized with social and institutional actors by random sampling); semi-structured questionnaires were applied to pluriactive families and interviews with department representatives of Infrastructure, Agriculture and Planning of Municipalities of the region, trade unions, associations and cooperatives. The findings indicate that there was an improvement in the area of quality of life by adopting pluriactive practices with the presence of social capital among pluriactive families. However, there was no formal and strategic planning in the territories to unite families around pluriactive activities nor to fortify social capital to combat rural poverty.